Formulation of Semi-Purified Diets for Striped Bass, Morone saxatilis, Larvae - Ashraf, Muhammad; Bengtson, David; Simpson, K.L. (Pakistan Journal of Nutrition, 2009)
Recent years have witnessed a dramatic rise in the intensive culture of striped bass, Morone saxatilis due to its reduced supply from capture fisheries and high market price. One of the major problems that limit its mass culture is non-availability of seed in sufficient quantities due to unreliability of live feeds and their high cost, Artemia for example. The main objective of these studies was, complete replacement of live food with artificial diets or at least reduce its quantity in larval food without compromising growth and survival of fish. Based on the chemical composition of natural zooplankton, the presumed ideal diet for striped bass larvae. various iso-caloric and iso-nitrogenous semi-purified diets were formulated. The chemically analyzed ingredients were homogenously blended, microencapsulated and fed to larval fish. Commercial starter diets were also used for comparison. There were two feeding trials. Eight and 12-day-old striped bass was used in trial 1 and 2 respectively. Former had 9 dietary treatments and was continued for two weeks. Instar I live Artemia nauplii and zooplankton served as control while their encapsulated forms were secondary controls. Fish fed on live Artemia and zooplankton exhibited the highest growth and survival comparatively lower in zooplankton fed group. Encapsulated live food ranked second. Fish in the rest of the treatments could gain only 0.1-5.8 mg and survival ranged just from 25-43%. Later trial, on the other hand, had 11 treatments and lasted four weeks. Same age and weight larval fish, were fed on live Artemia (control) nauplii, Artemia capsules and casein based semi-purified diet. All the diets were processed following the same procedures as implied in former trial. But unlike previous trial tannic acid was incorporated in encapsulation material of some of the diets to enhance capsule stability and dropped in others. Similarly betain was included in selected inert diets to boost diet acceptability. Some of the inert diets were also periodically supplemented with live Artemia nauplii. Fish reared on live Artemia maintained its superiority in growth and survival over its counterparts. Tannic acid containing diets with periodic supplementation of live Artemia gave 40-50% survival and reasonable growth while performance in rest of the treatments remained very poor. Fish grew only up to 11-25 mg and survival could not exceed 25%. It appears that striped bass larvae can not digest microcapsules due to poorly developed digestive system.